The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/mnras/stz3155
|View full text |Cite
|
Sign up to set email alerts
|

Young stars as tracers of a barred-spiral Milky Way

Abstract: Identifying the structure of our Galaxy has always been fraught with difficulties, and while modern surveys continue to make progress building a map of the Milky Way, there is still much to understand. The arm and bar features are important drivers in shaping the interstellar medium, but their exact nature and influence still require attention. We present results of smoothed particle hydrodynamic simulations of gas in the Milky Way including star formation, stellar feedback, and ISM cooling, when exposed to di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 127 publications
2
14
0
Order By: Relevance
“…It is nontrivial to disentangle the signatures of the Galactic bar and spiral structure, especially when the number of spiral arms and nature of the spiral structure itself remain uncertain. Similarly, Pettitt, Ragan & Smith (2020) showed that global features in velocity space unveiled by Gaia could be equally well reproduced by spiral or bar features.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is nontrivial to disentangle the signatures of the Galactic bar and spiral structure, especially when the number of spiral arms and nature of the spiral structure itself remain uncertain. Similarly, Pettitt, Ragan & Smith (2020) showed that global features in velocity space unveiled by Gaia could be equally well reproduced by spiral or bar features.…”
Section: Introductionmentioning
confidence: 87%
“…It is entirely possible (and likely) that some of this kinematic substructure arises from spiral structure (e.g. Sellwood et al 2019;Pettitt et al 2020) but it should not be assumed that they mark the current location of spiral arms. Following this transformation, we now have a map of the kinematic response to the potential, not the potential itself.…”
Section: Gaia Dr2 In Projected Action-angle Space (X Act Y Act )mentioning
confidence: 99%
“…It has been shown in numerous previous works that bars can influence the dynamics of gas out to the OLR (e.g. Koda & Wada 2002;Pettitt et al 2020), which could change the trends in streaming motions in their analysis (performed between 6-8 kpc) compared to what would be seen in a spiral-only model. Secondly, their arms are quite weak compared to the static spiral they use for comparison, with numerous interarm branches and wide density peaks.…”
Section: Disc Kinematicsmentioning
confidence: 99%
“…Tidal forces exerted in such interactions can readily create two-armed spiral features (Toomre & Toomre 1972;Struck, Dobbs & Hwang 2011;Pettitt & Wadsley 2018) and such a mechanism is likely to have played a role in some of the more well-known spiral galaxies such as M51 and M81 (Yun 1999). Bars can also drive spiral features in discs, particularly in the gas (Wada & Koda 2001;Pettitt, Ragan & Smith 2020), though for this study we limit ourselves to bar-free systems where the origin of spirality is more ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…-era understanding of the Galactic bar also suggests slower pattern speeds than assumed in earlier works, which place corotation as far out as 6 kpc (Sanders et al 2019;Bovy et al 2019). The ISM responds strongly to the motion of the bar out to corotation, and even as far as the more distant Outer Lindblad Resonance for certain models of bars (Sormani et al 2015;Pettitt et al 2020). Any spiral arm-like features are thus inherently coupled to the bar within at least corotation and more sophisticated modelling is required to fully understand the kinematics of the gas.…”
Section: Sedigism ℓ Mapsmentioning
confidence: 79%